Transformasi Karakter dalam The Wonderful Story of Henry Sugar: Kajian Hermeneutika Paul Ricoeur - Permadikusumah, Mu'afa Audia; Supiarza, Hery; Anelina, Nazla Vania (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
This study explores the transformation of the protagonist in Wes Anderson's short film The Wonderful Story of Henry Sugar (2023), through the lens of Paul Ricoeur's hermeneutic arc. The film narrates the spiritual and existential journey of Henry Sugar, a wealthy man who shifts from materialism to altruism after discovering a meditative technique that allows him to see without using his eyes. Initially motivated by greed and self-interest, Henry experiences a profound internal transformation that leads him to use his abilities for philanthropic purposes. The study employs a qualitative descriptive method, focusing on narrative analysis supported by Ricoeur’s three-phase interpretative framework: explication, understanding, and appropriation. Findings suggest that Henry’s transformation embodies a significant ethical and existential shift, highlighting the film's critique of consumerism and spiritual emptiness. Moreover, Anderson’s distinctive aesthetic—marked by symmetrical compositions, pastel palettes, and theatrical mise-en-scène—reinforces the symbolic depth and moral trajectory of the narrative. This research underscores how cinema can be interpreted as a reflective medium that facilitates ethical contemplation and personal meaning-making through character development. Ultimately, the study affirms that The Wonderful Story of Henry Sugar functions not only as artistic storytelling but also as a philosophical exploration of purpose, morality, and the transformative potential of self-discovery.